PENGGUNAAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS SOFTWARE LIVEWORKSHEET UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Yeyen Nurtanto; Sri Suneki (STKIP Subang, 2024)
E-LKPD or digital-based student worksheets are one of the innovations in the world of education in the 21st century. One of them is LKPD based on Liveworksheet software, which is a platform that can help teachers use it to create effective and interactive learning. With a variety of features that can be used and a more attractive appearance, this application is expected to increase student activity so that they can improve learning outcomes optimally. This research aims to identify student learning outcomes through the use of LKPD based on Liveworksheet software. In this research, the method used is library research, where library research is a method used by collecting various sources of data or theories that support the formation of this scientific work. This type of research is qualitative research. Then the discussion in this research is obtained from various information through 5 (five) journals regarding the use of E-LKPD Liveworksheet in improving student learning outcomes. Furthermore, researchers obtained information that students' learning outcomes increased when using E-LKPD Liveworksheet during learning. By using student worksheets based on live worksheet software, it is hoped that they can provide varied and innovative ways and strategies to each teacher as a teacher in the classroom learning process.